Bộ điều khiển tối ưu bền vững cho hệ thống điều khiển số có trễ - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper presents a method of designing robust optimal controllers for digital control systems with control delay. A predictor similar to the Smith one is used. The robust optimal state feedback control law is obtained by dynamic programming method. The uncertainty in system parameters is taken care of by an additional term in the Riccati equation. The case of output feedback controller is also dicussed.